Global economic policy uncertainty and fiscal responses in emerging markets: A dynamic error-correction panel - Alsubaie, Ali (Universitas Islam Indonesia, 2026)
Purpose — This study examines how global economic policy uncertainty (GEPU) shapes government expenditure dynamics in emerging market economies. Methods — Using an annual panel of 28 emerging economies from 1998 to 2023, this study analyzes short-run fiscal adjustments and long-run equilibrium relationships between global uncertainty and public expenditure. To address challenges arising from mixed integration orders and cross-sectional dependence driven by global shocks, it employs a multistage empirical strategy that combines fixed-effects estimation, Driscoll–Kraay robust inference, and a cross-sectionally augmented dynamic error-correction model (ECM).Findings — The results provide robust evidence that higher GEPU is associated with higher government expenditure as a share of Gross Domestic Product (GDP). This relationship holds across alternative specifications and persists in the long run, indicating that fiscal responses to uncertainty are not purely transitory. Dynamic estimates reveal a statistically significant error-correction mechanism, confirming a stable long-term relationship among government expenditure, global uncertainty, and domestic economic conditions. Structural factors, particularly urbanization, further shape fiscal outcomes, whereas income per capita enters with a negative sign, though its effect is not consistently statistically significant across specifications.Implication — The findings have important implications for fiscal sustainability and policy design in an increasingly uncertain global environment.Originality — By explicitly accounting for non-stationarity and unobserved common global factors, this study contributes to the literature by providing new evidence of how emerging market governments respond to global risks.